Theories of cognition in the later Middle Ages - Pasnau, Robert (Cambridge, Cambridge University Press, 1997)
This book is a major contribution to the history of philosophy in the later medieval period (1250-1350). It focuses on cognitive theory, a subject of intense investigation during these years. In fact, many of the issues that dominate philosophy of mind and epistemology today - intentionality, mental representation, skepticism, realism - were hotly debated in the later medieval period. The book offers a careful analysis of these debates, primarily through the work of Thomas Aquinas, Peter John Olivi, and William Ockham. Both Olivi and Ockham attempt to reconceptualize cognition along direct realist lines, criticizing in the process standard Aristotelian accounts of the sort proposed by Aquinas
Though of primary interest to medieval philosophers, the book presupposes no background knowledge of the medieval period, and will therefore interest a broader community of philosophers concerned with the origins of contemporary cognitive theory
1. Immateriality and intentionality -- 2. Intentionality made mysterious -- 3. Form and representation -- 4. Passivity and attention -- 5. Are species superfluous? -- 6. Aquinas and direct realism -- 7. The veil of species -- 8. Word and concept -- App. A. The identity of knower and known (Aquinas) -- App. B. Henry of Ghent and intelligible species
Includes bibliographical references (p. 311-319) and index
Keywords: Thomas, -- Aquinas, Saint, -- 1225?-1274; Olivi, Pierre Jean, -- 1248 or 1249-1298; William, -- of Ockham, -- approximately 1285-approximately 1349; Knowledge, Theory of -- History; Cognition -- History; Philosophy, Medieval; Knowledge -- history; Cognition -- history; Philosophy -- history; History